Chemical warfare agent research in precision‐cut tissue slices—a useful alternative approach. Issue 1 (17th August 2020) - Herbert, Julia; Laskin, Debra L.; Gow, Andrew J.; Laskin, Jeffrey D.
Abstract: The use of chemical warfare agents (CWAs) in military conflicts and against civilians is a recurrent problem. Despite ongoing CWA research using in vitro or in vivo models, progress to elucidate mechanisms of toxicity and to develop effective therapies, decontamination procedures, and general countermeasures is still limited. Novel scientific approaches to address these questions are needed to expand perspectives on existing knowledge and gain new insights. To achieve this, the use of ex vivo techniques like precision‐cut tissue slices (PCTSs) can be a valuable approach. Existing studies employing this economical and relatively easy to implement method show model suitability and comparability with the use of in vitro and in vivo models. In this article, we review research on CWAs in PCTSs to illustrate the advantages of the approach and to promote future applications.